Linking Self-Efficacy, Entrepreneurial Knowledge, and Social Media Use to Entrepreneurial Intention Through Self-Confidence - Amatullah, Amatullah; Isma, Andika; Kemalasari, Andi Anggi; Asmayanti, Asmayanti; Karangan, Winda (Universitas Negeri Makassar, 2025)
Entrepreneurship plays an important role in strengthening competitiveness, generating employment opportunities, and encouraging innovation in the modern economy. Along with the rapid development of digital technology, social media has become an increasingly relevant platform for entrepreneurial learning, business promotion, and opportunity recognition. This study examines the effects of self-efficacy, entrepreneurial knowledge, and social media use on entrepreneurial intention, with confidence positioned as a mediating variable. A quantitative explanatory approach was employed using data collected from 97 respondents selected through proportional random sampling. The study used a structured questionnaire as the main research instrument, and the data were analyzed to assess both direct and indirect relationships among variables. The findings reveal that self-efficacy, entrepreneurial knowledge, and social media use have significant effects on entrepreneurial intention, both directly and indirectly through confidence. The results also show that confidence serves as an important psychological mechanism that strengthens the relationship between individual capability, entrepreneurial understanding, digital engagement, and the intention to start a business. These findings suggest that efforts to foster entrepreneurial intention should not only focus on improving knowledge and digital literacy, but also on building stronger personal confidence in entrepreneurial capability. This study provides practical implications for higher education institutions in designing entrepreneurship programs that integrate capability development, digital exposure, and confidence-building strategies to encourage stronger entrepreneurial intention.